Penentuan Waktu Standar Pemasangan Sambungan Baru di PDAM Kabupaten Karanganyar - Sofyan Arifin; Irwan Iftadi; Yuniaristanto - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
To meet the needs of clean water for the community Karanganyar then PDAM are trying to expand the water distribution network to customers. In the process of acceptance of new customers has been running smoothly, but the taps have not been able to determine the standard time for the new connections. Sub section in Karanganyar taps involved in the splicing process of which this new relationship Subscriptions Subdivision, Subdivision Planning Engineering, Sub-Division of Logistics and Engineering Subdivision House Connection The method used to calculate the standard time in this study is the method Stopwatch and Interview Study and the employee concerned about the daily job performance. Study stopwatch method used to measure the standard time and Subscriptions Relations Sub-Division and Sub-Division of Logistics, due to the work carried out is done only monotonous and not affected by the queue of applicants for new connections or constraints that occur in the field. While the second method is to interview employees concerned about job performance daily use on Sub Division of Engineering and Technical Planning House Connection. Because the process of their work in direct contact with the ground and changing conditions. The results of the study time required in subsection subscription relationship is 88,05 minutes, sub-section survey engineering planning division 52 minutes, and the division RAB is 60 minutes, subpart logistics takes 92.10 minutes and sub-section home connection is 60 minutes. But the process is carried out on different days, so the beginning of the registration process takes up to 4 days attached. But the implementation of the taps that during this run takes 1-2 weeks. Proposed improvements to the taps are made additional employees in the sub-section on the logistics and scheduling of sub-section design and engineering techniques so that the connection is more orderly process